7.2k views
1 vote
Find f(g(3)) for the functions f(x) =3x+8 and g(x) =-x^3

1 Answer

6 votes

We are given:

f(x) = 3x + 8

g(x) = -x³

__________________________________________________________

The Concept:

We have to find the values of f(g(3)), which means that we have to apply the function g() on 3 and apply the function f() on the value we get.

Finding f(g(3)):

Finding g(3):

g(x) = -x³

g(3) = -(3)³

g(3) = -27

Finding f(g(3)):

f(x) = 3x + 8

f(g(3)) = 3(g(3)) + 8

f(g(3)) = 3(-27) + 8

f(g(3)) = -81 + 8

f(g(3)) = -73

Hence, f(g(3)) = -73

User Anil Kesariya
by
5.3k points